Pengaruh Pentingnya Literasi Keuangan dan Aplikasi Shopee Terhadap Perilaku Konsumtif Mahasiswa Ekonomi Semester VIII Universitas Bhinneka PGRI - Fuadi, Muchammad Riyadh Hayatul; Subagyo, Siswo (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
In the era of digitalization, the role of financial literacy helps individuals to understand and manage the complexity of the modern economy This study aims to analyze the influence of the importance of financial literacy and the use of the Shopee application on the consumptive behavior of students in the eighth semester of the Economics Education Study Program, Bhinneka University PGRI Tulungagung. The method used is quantitative with a descriptive approach. The data obtained from the questionnaire or questionnaire was distributed to 89 students. The results of the analysis showed that there was no significant influence between Financial Literacy (XI) and Consumptive Behavior (Y). with a calculated t value of (1.228) which is smaller than the t table and a significance value (0.223). The Shopee application has a significant effect on Consumptive Behavior, with a calculated t value of (2.585) which is greater than the t table and a significance value of (0.011). Simultaneously, these two variables made a significant contribution to Consumptive Behavior, with a calculated F value of (6.734) which was greater than the F of the table (3.103) and a significance value of (0.002). Therefore, it can be concluded that financial literacy does not have a significant effect on Consumptive Behavior, while the use of the Shopee application has a significant influence. Simultaneously, the two variables simultaneously have a significant effect on student consumptive behavior. These findings indicate that despite high financial literacy, the use of online shopping applications remains the dominant factor driving consumptive behavior.